Estradiol decreases the excitability of RA projection neurons in adult male zebra finches - Zhang, Yutao; Sun, Yalun; Wu, Yanran; Sun, Wei; Zhang, Kun; Meng, Wei; Wang, Songhua (Frontiers in Cellular Neuroscience, 2023)
Zebra finches are essential animal models for studying learned vocal signals. The robust nucleus of the arcopallium (RA) plays an important role in regulating singing behavior. Our previous work showed that castration inhibited the electrophysiological activity of RA projection neurons (PNs) in male zebra finches, demonstrating that testosterone modulate the excitability of RA PNs. Testosterone can be converted into estradiol (E2) in the brain through aromatase; however, the physiological functions of E2 in RA are still unknown. This study aimed to investigate the electrophysiological activities of E2 on the RA PNs of male zebra finches through patch clamp. E2 rapidly decreased the evoked and spontaneous action potential (AP) of RA PNs, hyperpolarized the resting membrane potential, and decreased the membrane input resistance. Moreover, the G protein–coupled membrane-bound estrogen receptor (GPER) agonist G1 decreased both the evoked and spontaneous AP of RA PNs. Furthermore, the GPER antagonist G15 had no effect on the evoked and spontaneous AP of RA PNs; E2 and G15 together also had no effect on the evoked and spontaneous AP of RA PNs. These findings suggested that E2 rapidly decreased the excitability of RA PNs and its binding to GPER suppressed the excitability of RA PNs. These pieces of evidence helped us fully understand the principle of E2 signal mediation via its receptors to modulate the excitability of RA PNs in songbirds.